Recent Progress in Flexible Multiferroics - Jana, Biswajit; Ghosh, Kritika; Rudrapal, Krishna; Gaur, Pallavi; Shihabudeen, P. K.; Roy Chaudhuri, Ayan (Frontiers in Physics, 2022)
A great deal of interest has grown in both academia and industry towards flexible multiferroics in the recent years. The coupling of ferromagnetic properties with ferroelectric properties in multiferroic materials opens up many opportunities in applications such as, magnetoelectric random access memories, magnetic field sensors, energy harvesters, etc. Multiferroic materials on a flexible platform bring an exciting opportunity for the next generation of consumer electronics owing to their unique characteristics of wearability, portability, and weight reduction. However, the fabrication of flexible multiferroic devices is still a great challenge due to various technical difficulties, including the requirement of high growth temperature of the oxide based multiferroic materials, their lattice mismatch with the flexible substrates, and the brittleness of the functional layers. In this review article, we shall discuss different methods of fabricating flexible or even freestanding oxide films to achieve flexible electronics. This article shall address the benefits and challenges of each synthesis method in terms of interlayer interactions and growth parameters. Further, the article shall include an account of the possible bending limits of different flexible substrates without degrading the properties of the functional layer. Finally, we shall address the challenges, opportunities and future research directions in flexible multiferroics.